MORPHOLOGICAL CHARACTERISTICS ENDOCRINOCYTES PANCREAS TO DISTANT MEDICAL CORRECTION TERMS OF DIABETES - Попович, Ю. І.; Іванців, О. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The morphological changes of the pancreas, which developed in experimental diabetes (ETSD) and its treatment with insulin and exenatide, where the long injection morphologically revealed improving carbohydrate metabolism and increased regenerative processes in islets of the pancreas that were studied. The proof of this is the increase in the average area of the islands (mkm.,sq), the average number of islands per 1 mm.,sq, the relationship of betta cells / alpha cells during the experiment and partial reconstruction of typical ultrastructural endocrinocytes of pancreatic islands.